2017
DOI: 10.1101/mcs.a002055
|View full text |Cite
|
Sign up to set email alerts
|

Genomic analysis of an infant with intractable diarrhea and dilated cardiomyopathy

Abstract: We describe a case of an infant presenting with intractable diarrhea who subsequently developed dilated cardiomyopathy, for whom a diagnosis was not initially achieved despite extensive clinical testing, including panel-based genetic testing. Research-based whole-genome sequences of the proband and both parents were analyzed by the SAVANNA pipeline, a variant prioritization strategy integrating features of variants, genes, and phenotypes, which was implemented using publicly available tools. Although the intes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…Variants were annotated using ANNOVAR version 2016-02-04 ( Wang et al 2010 ) as previously described ( Bodian et al 2017 ), with the following updates. Transcript models were obtained from the ANNOVAR-provided RefSeq gene ( O'Leary et al 2016 ) and Ensembl ( Yates et al 2016 ) databases, version 2017-06-01, and GenCode ( Harrow et al 2012 ) wgEncodeGencodeCompV24lift37, downloaded from the UCSC genome browser ( Kent et al 2002 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Variants were annotated using ANNOVAR version 2016-02-04 ( Wang et al 2010 ) as previously described ( Bodian et al 2017 ), with the following updates. Transcript models were obtained from the ANNOVAR-provided RefSeq gene ( O'Leary et al 2016 ) and Ensembl ( Yates et al 2016 ) databases, version 2017-06-01, and GenCode ( Harrow et al 2012 ) wgEncodeGencodeCompV24lift37, downloaded from the UCSC genome browser ( Kent et al 2002 ).…”
Section: Methodsmentioning
confidence: 99%
“…Transcript models were obtained from the ANNOVAR-provided RefSeq gene ( O'Leary et al 2016 ) and Ensembl ( Yates et al 2016 ) databases, version 2017-06-01, and GenCode ( Harrow et al 2012 ) wgEncodeGencodeCompV24lift37, downloaded from the UCSC genome browser ( Kent et al 2002 ). Small variants and CNVs predicted to impact the protein sequence of any transcript or that are reported as pathogenic or likely pathogenic in the ClinVar 201705 xml file ( Landrum et al 2016 ) were identified using SAVANNA as described ( Bodian et al 2017 ). Briefly, variants were required to have minimum read depth of ≥6, allele balance of ≥0.225, a maximum allele frequency of 0.02 in the gnomAD genomic dataset ( Lek et al 2016 ), and the data sets provided in the ANNOVAR file popfreq_all_2015_0413, including the 1000 Genomes Project genomes ( Auton et al 2015 ) and in internal WGS databases.…”
Section: Methodsmentioning
confidence: 99%
“…Candidate variants were required to lie in genes previously associated with cardiac conditions, using a predefined gene list (Table ) created in part by genes noted in the following publications (Lalani & Belmont, ; Topf et al., ), complemented by literature searches of genes with candidate variants that pass the filtering criteria. The variants were required to have low frequency (<1%) in control populations, and to meet published sequencing quality criteria (Bodian et al., ). Potentially damaging variants in known cardiac genes were defined as rare variants (MAF <0.001 in gnomAD) (Lek et al., ) that were either predicted to be deleterious by MetaSVM (Kim, Jhong, Lee, & Koo, ), or annotated as splice site, frameshift, nonframeshift, or stopgain (Table ).…”
Section: Methodsmentioning
confidence: 99%
“…An analysis of the 72 previously reported CTE patients (AlMahamed & Hammo, ; Al‐Mayouf, Alswaied, Alkuraya, AlMehaidib, & Faqih, ; Bodian et al., ; d'Apolito et al., ; Ko et al., ; Pêgas et al., ; Salomon et al., ; Salomon et al., ; Schnell et al., ; Shakhnovich, Dinwiddie, Hildreth, Attard, & Kingsmore, ; Sivagnanam et al., ; Sivagnanam et al., ; Tang, Huang, Xu, & Huang, ; Thoeni et al., ) along with the 17 novel patients reported here is consistent with the expected genetics of an autosomal recessive disease (Figure ; Supporting Information Table ). Many CTE patients (60 of 90 patients) were homozygous for EPCAM mutations, and most of the remainder were compound heterozygotes (24 of 90 patients).…”
Section: Variants Of Epcam In Human Diseasementioning
confidence: 99%